Efeitos da atividade física sobre equilíbrio, risco de quedas e função cognitiva de idosos com demência de Alzheimer: Salma Stéphany Soleman Hernandez. - - Soleman Hernandez, Salma Stéphany [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The Alzheimer’s dementia represents a clinical condition inherent to many chronic and neurodegenerative diseases that are usually related to a decline in the cognitive and physical functions. The objective of this experimental design research was to analyze the effects of a regular and systemized physical activity program over the cognitive functions, balance and risk of falls of elderly with Alzheimer’s Dementia (DA). The sample was made of 16 elderly with DA, distributed in two groups: a) intervention group – GI (9 subjects that had participated in a program of physical activity, that consisted of 3 weekly sessions of 60 minutes each, in alternated days and with a duration of 6 months); b) control group – GC (7 subjects that did not participate in the program of physical activity). Both groups maintained the doctoral and pharmacological assistance routine. The subjects passed through two different evaluations (pre and post-intervention) the questionnaire (Mini-exam of Mental State for cognitive functions) and motor tests (Berg Functional Balance Scale – EEFB, Timed Up-and-Go (TUG) time (TUGs) and steps (TUGp) and the test of agility and dynamic balance (AGILEQ) of the American Alliance for Health, Physical Education Recreation and Dance for elderly). The obtained results were, respectively in the pre and post-intervention moments: a) AGILEQ (GI = 39,1 ± 10,2 and 38,4 ± 8,9 and GC = 45,6 ± 16,7 and 59,9 ± 22,0 seconds) with the statistically interaction significant (ANOVA two-way; F1,14 = 32,07; p=0,01) between groups and moments; b) TUGs (GI = 9,8 ± 2,5 and 9,5 ± 3,3 and GC = 10,6 ± 4,5 and 12,7 ± 7,3 seconds) the test UMann Whitney did not appoint any significant differences between the groups in the post-intervention moment, however the analyzes of Wilcoxon evidenced a ...(Complete abstract click electronic access below)

A demência de Alzheimer representa uma condição clínica inerente a muitas doenças crônicas e neurodegenerativas que comumente está relacionada a um declínio das funções cognitivas e físicas. Este estudo de delineamento experimental teve como objetivo analisar os efeitos de um programa de atividade física regular e sistematizado sobre as funções cognitivas, equilíbrio e risco de quedas de idosos com demência de Alzheimer (DA). A amostra foi constituída por 16 idosos com DA, distribuídos em dois grupos: a) grupo intervenção – GI (9 idosos que participaram de um programa de atividade física, 3 sessões semanais de 60 minutos cada, em dias alternados e com duração de 6 meses; b) grupo controle – GC (7 idosos que não participaram do programa de atividade física). Ambos os grupos mantiveram a assistência médica e farmacológica rotineira. Os participantes realizaram duas avaliações (pré e pós-intervenção) do tipo questionário (Mini-exame do Estado Mental para funções cognitivas) e testes motores (Escala de Equilíbrio Funcional de Berg - EEFB, Timed Up-and-Go (TUG) tempo (TUGs) e passos (TUGp) e o teste de Agilidade e Equilíbrio Dinâmico (AGILEQ) da bateria de testes para idosos da American Alliance for Health, Physical Education Recreation and Dance. Foram obtidos os seguintes resultados, respectivamente nos momentos pré e pósintervenção: a) AGILEQ (GI = 39,1 ± 10,2 e 38,4 ± 8,9 e GC = 45,6 ± 16,7 e 59,9 ± 22,0 segundos) com interação estatisticamente significativa (ANOVA two-way; F1,14 = 32,07; p=0,01) entre grupos e momentos; b) TUGs (GI = 9,8 ± 2,5 e 9,5 ± 3,3 e GC = 10,6 ± 4,5 e 12,7 ± 7,3 segundos) o teste U-Mann Whitney não apontou diferenças significantes entre os grupos no momento pós-intervenção, contudo a análise ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação física adaptada; Alzheimer, Doença de; Atividade física -Doença de Alzheimer; Abordagem motora; Atividade física - Capacidade funcional; Physical activity - functional capacity